FISIOTERAPI PADA BRONKIOLITIS: NEBULIZER, INFRARED, POSTURAL DRAINAGE, DAN TAPPOTEMENT - Cahya, Andika Bayu Dwi (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Bronchiolitis is a lower respiratory tract infection commonly found in infants and young children. Objective: This study aimed to evaluate the effectiveness of physiotherapy management in a bronchiolitis case using nebulizer, infrared therapy, postural drainage, and tapotement modalities. Method: The method used is a case study involving a patient (An. A) at Balkesmas Semarang presenting with shortness of breath, coughing, and excessive sputum production. Result: After five physiotherapy sessions, there was a noticeable decrease in cough intensity, sputum production, and respiratory rate. Conclusion: These findings suggest that the combination of physiotherapy modalities is effective in improving the clinical condition of bronchiolitis patients.